Answer:
1. Add 1 to both sides
2. Multiply both sides by 4
3. Take the square root of both sides
4. Subtract 5 from both sides
Step-by-step explanation:
![\frac{1}{4} (x+5)^{2} -1=3](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B4%7D%20%28x%2B5%29%5E%7B2%7D%20-1%3D3)
<em>Add 1 to both sides</em>
![\frac{1}{4} (x+5)^{2}=4](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B4%7D%20%28x%2B5%29%5E%7B2%7D%3D4)
<em>Multiply both sides by 4</em>
![(x+5)^{2}=16](https://tex.z-dn.net/?f=%28x%2B5%29%5E%7B2%7D%3D16)
<em>Square root both sides</em>
![x+5=4](https://tex.z-dn.net/?f=x%2B5%3D4)
<em>Subtract 5 from both sides</em>
![x=-1](https://tex.z-dn.net/?f=x%3D-1)